Rosette inhibition test in chronic liver disease. - Salerno, F (1976)
A role has recently been assigned to cell-mediated immunity in chronic liver diseases in addition to the well-known alterations of humoral immunity. We now report the results of the rosette inhibition test for the evaluation of T-lymphocyte "sensitization" in patients with different chronic liver disorders. A cell-mediated immune reaction was found in 81% of patients with chronic active hepatitis and in 71% with primary biliary cirrhosis, whereas patients with chronic persistent hepatitis showed no reaction. The correlation with the incidence of hepatitis B antigen showed that T-lymphocyte sensitization was more frequent in the group of HB-positive patients. Finally, improvement of the test was observed in four out of nine patients given immunosuppressive treatment.